Pengaruh Comprehensive Stakeholder Pressure dan Corporate Governance terhadap Kualitas Sustainability Report - Natalia, Herlinda Putri; Dura, Justita (Universitas Muhammadiyah Metro, 2023)
The aim of this study is to examine the effect of comprehensive stakeholder pressure and corporate governance on the quality of sustainability reports for LQ45 companies on the Indonesia Stock Exchange for the 2019-2021 period. The comprehensive stakeholder pressure component consists of shareholders and employees, while the corporate governance component consists of the board of commissioners and the audit committee. The sampling technique used purposive sampling method with a sample of 75 companies and data analysis techniques using linear regression. This research uses legitimacy theory and stakeholder theory. The results showed that the components of shareholders, employees, the board of commissioners and the audit committee had no effect on the quality of the sustainability report. Limitations in the study, namely not all LQ45 companies disclose sustainability reports and the lack of variables in the study. Suggestions for future researchers can focus on companies that have disclosed sustainability reports and can use more other variables so they can provide further explanation about the factors that affect the quality of sustainability reports so they can provide more accurate information.